Towards control of the global HIV epidemic: Addressing the middle-90 challenge in the UNAIDS 90-90-90 target. - Collins Iwuji; Marie-Louise Newell (PLoS Medicine, 2017)
In a Perspective, Collins Iwuji and Marie-Louise Newell discuss early findings from Richard Hayes and colleagues' PopART study on HIV testing and treatment.